Association between health-related quality of life and psychological distress at different stages of chronic kidney disease - Norhayati Ibrahim; Rafidah Aini Pakri Mohamed; Teo, Sharlene; Normah Che Din; Abdul Halim Abdul Gafor; Rozmi Ismail; Zahara Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2016)
The prevalence of chronic kidney disease (CKD) have increased and become one of the major public health concerns worldwide including Malaysia. Previous studies on CKD generally focused on patients who were already undergoing dialysis treatment; however, studies investigating the stresses experienced by pre-dialysis CKD patients were limited. This study aimed to examine the prevalence of psychological distress and their association with the Health Related Quality of Life (HRQoL) during the different stages of CKD. This cross-sectional study involved 200 pre-dialysis patients from stages 3 to 5, who were recruited from the Nephrology Clinic at the National University of Malaysia Medical Centre (UKMMC). The instruments used in this study were the Short Form 36 (measuring HRQoL) and Hospital Anxiety and Depression Scale (HADS) to measure the psychological distress. The results showed that the prevalence of depression and anxiety increased proportionally with the CKD stages. The HRQoL sub-component scores declined as the CKD stages increased except for social functioning. An impaired HRQoL was associated with depression and anxiety in the CKD patients. The results suggested that it is very important to manage kidney disease at an early stage and that a healthier lifestyle is adopted.